DIGITAL MARKETING AND INDONESIA’S YOUTH ENTREPRENEURS’ BUSINESS - Prathivi, Maria Dini Gilang (Universitas Brawijaya, Indonesia, 2020)
ASEAN's goals to beone stop market and production base, a highly competitive region, with a great economic development brings an urgency for every company in Indonesia to utilize technology for the sake of their company growth. The implementation of digital marketing is one of the technology utilizations that the company nowadays bring into their business process. Ciputra University focuses on developing its student's businesses. According to their goals to produces graduates who have an entrepreneurial mindset thatis able to establish and manage a sustainable business, Ciputra University becomes one mini representation of the world of new business establishments in Indonesia developed by young people.By looking at how the implementation of digital marketing conducted by Ciputra University's students as startup scale business owners in the city of Surabaya, researchers found the impact on digital marketing toa very interesting characteristic of youth entrepreneur business performance. This research found that digital marketing implementation relates positively tothese youth entrepreneur business achievements such as increased sales and profit, enlarged market share, deepen customer loyalty, and escalated competitive advantage.